AMERICAN DREAM: THE AMERICAN HEGEMONIC CULTURE AND ITS IMPLICATIONS TO THE WORLD - Kasiyarno . (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2014)
A nation could be a great one as long as it has a great dream. The best example for this is America. Through its long history, it manages to realize a dream to be a superpower. It can be said that “American Dream” is one of the most significant features for the growth of a “constantly eyeing for winner” culture. American Studies experts call it as a “hegemonic culture” in which American norms, values and cultural practices are considered superior against the world culture. Globalizing the culture has been the most effective engine to spread American cultural values and to shape the global civilizations. Using American Studies perspective, this paper attempts to review the extent to which the “American Dream” has successfully established Americanization, as well as how the hegemonic culture has influenced the lives of peoples across the world in the form of popular culture.